Efecto físico-químico y organoléptico de tres tipos de grasa en bastones fritos de dos variedades de camote - Cedeño Guerrero, Ronny Alejandro (2023)
The purpose of the research was to evaluate the physicochemical and organoleptic effect produced by three types of fats in fried sticks of two sweet potato varieties. The factors under study were types of frying fats and variety of sweet potato, A x B factorial arrangement was applied in a Completely randomized Design, with three repetitions resulting in 18 experimental units and in each experimental unit 1Kg of sweet potato was used in one liter of oil. and/or fat to carry out the frying process for 7 minutes at 180ºC. The physicochemical variables evaluated through statistical analysis were: fat, humidity and hardness. Factor A (types of fat) influences the fat variable of sweet potato fried sticks, however, in the humidity variable, neither the factors nor the treatments showed significant differences; factor B (type of sweet potato) causes an effect on the hardness of sweet potato fried sticks. Through the acceptability analysis carried out by untrained tasters, it was evidenced that T2 and T5 were better treatments, the same ones that stood out and were better qualified in the evaluated attributes (product appearance and taste), while in the odor and color category the ones with the best acceptability were T5 and T1 respectively.